Benefits and Application of IoB in Educational Businesses: Smart, Sustainable, and Personalized Learning - ZAHRA SADEQI-ARANI; REZA VAHIDNIA; ESMAEIL MAZROUI NASRABADI (Journal of Advances in Medical Education and Professionalism)
The emergence of the Internet of Behaviors (IoB) has created new opportunities for influencing and guiding human decisionmaking. IoB refers to the collection, analysis, and application ofdata generated by individuals’ online activities, behaviors, and interactions. This concept integrates data from various sources, including social media, wearable devices, smartphones, andother digital platforms, to gain insights into human behavior patterns. This technology can profoundly affect various areas of our lives, such as healthcare, education, and transportation. Thispaper explores the transformative potential of IoB in educational businesses, where it enables personalized learning, real-time feedback, and improved student retention. By analyzing data onstudent engagement and performance, IoB supports differentiated instruction, enhances collaborative learning, and drives datadriven curriculum development. Additionally, IoB contributes to students’ health and safety through wearable technology and promotes smart, resource-efficient classrooms. However, the implementation of IoB in education poses significant challenges, including privacy concerns, technical complexities, and access disparities. The paper identifies key areas for future research, such as the integration of IoB with traditional pedagogical approaches, equitable access to IoB technologies, and development of ethical standards to safeguard student privacy. This commentary underscores IoB’s potential to revolutionize education while emphasizing the need for careful consideration of its challenges to ensure broad and equitable benefits.